Identifikasi Senyawa Alelokimia pada Ekstrak Akar Sorgum Menggunakan GC-MS dan Evaluasi Potensinya sebagai Bioherbisida - Edi Susilo; Nanik Setyowati; Hesti Pujiwati (University of Prof. Dr. Hazairin, SH, 2026)
Weed control using synthetic herbicides has hurt the environment, prompting the need for more environmentally friendly weed management. This study aims to determine the allelochemical compounds contained in sorghum (Sorghum bicolor L.) root extract and analyze its potential as a bioherbicide. This study was conducted from July to September 2023 at the Faculty of Agriculture, Bengkulu University. Compound analysis used Gas Chromatography Mass Spectrometry (GC-MS). Root extraction was performed by maceration with methanol, and identification of organic compounds was performed by matching mass spectra to NIST. GC-MS analysis showed that sorghum root extract contained secondary metabolites with potential allelochemical activity, especially phenolics, organosulfur compounds, fatty acids, fatty acid amides, and alkaloids. Polar and semi-polar compounds with potential as water-based bioherbicides include 2-aminoethanethiol hydrogen sulfate (12.28%), 2,3-dihydro-1-benzofuran (2.16%), and phenol (1.40%). Furthermore, the dominant compounds identified were derived from unsaturated fatty acids, namely (9E)-9-octadecenoic acid (22.95%), trans-13-octadecenoic acid (16.48%), and 9-octadecenamide (5.67%), as well as indolizino-carbazole alkaloids (2.24%), suspected to contribute to phytotoxic activity due to disruption of cell membranes and metabolism of the target plant. This indicates that sorghum roots can serve as a natural source of bioherbicides to support a more sustainable weed control system.